2017
DOI: 10.1590/0102-33062016abb0456
|View full text |Cite
|
Sign up to set email alerts
|

Development of carpels and ovules in Dialypetalanthus fuscescens Kuhlm. (Rubiaceae): an enigmatic taxon

Abstract: Dialypetalanthus is a monospecifi c genus that occurs in the Amazon Basin of Brazil, Bolivia and Peru and occupies a controversial position among the Rubiaceae. We continue this taxonomic discussion with the overall aim of clarifying the systematic position of D. fuscescens within the Rubiaceae. To accomplish this, we analyzed the ontogeny of its gynoecium, in particular the fl oral meristem, as well as the development of the carpels and cauline placentation. Gynosporogenesis and the diff erentiation of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Only after the appearance of most stamens, the development of the gynoecium starts, similar as in other Rubiaceae (De Block and Vrijdaghs 2013;Vrijdaghs et al 2020), though without gynoecial nectary (Fig. 3C; Figueiredo et al 2017). Perhaps, investing in polyandry instead of a nectary gives an ecological advantage to Dialypetalanthus, but this is a subject for another study.…”
Section: Dialypetalanthusmentioning
confidence: 51%
See 2 more Smart Citations
“…Only after the appearance of most stamens, the development of the gynoecium starts, similar as in other Rubiaceae (De Block and Vrijdaghs 2013;Vrijdaghs et al 2020), though without gynoecial nectary (Fig. 3C; Figueiredo et al 2017). Perhaps, investing in polyandry instead of a nectary gives an ecological advantage to Dialypetalanthus, but this is a subject for another study.…”
Section: Dialypetalanthusmentioning
confidence: 51%
“…The ovary develops into a septicidal capsule with numerous winged seeds (e.g. Piesschaert et al 1997;Figueiredo et al 2017), features that are reminiscent of several rubiaceous genera, such as Mitragyna Korth. and other Naucleeae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…apical in Vanguerieae and basal in Psychotrieae. However, some anatomical and development studies have shown that placentation can also be extremely variable in Rubiaceae (Svoma 1991;Figueiredo et al 2013Figueiredo et al , 2017. According to Ronse Decraene and Smets (2000), in Rubiaceae, the basal, central, or apical placentation are the result of differential degrees of development among the basal placental portion of the ovary and the apical portion of the style.…”
Section: The New Species As a Member Of Chiococceae Sensu Latomentioning
confidence: 99%